2020
DOI: 10.1021/acs.est.0c00224
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Organic Pollutants in Waters Using the Diffusive Gradients in the Thin Films Technique: Investigations on the Effects of Biofouling and Degradation

Abstract: The diffusive gradients in thin films (DGT) passive sampling technique has been increasingly used to provide time-weighted average concentrations of the biorelevant fraction of organic contaminants in waters, with high spatial and temporal resolutions at low cost. This study was tested for the effects of biofouling and compound degradation/loss during sample handling/storage on the DGT measurement of a range of emerging organic pollutants. Biofouling was tested using biofilms collected from the influent and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…50 The analytes were also shown to have little degradation/loss in the sampling, transport and storage conditions of this study. 50 Therefore, the passive sampling system here is shown to have good QC. DGT sampling provides in situ TWA concentrations for the deployment period, e.g.…”
Section: Comparison Of Dgt and Grab Sampling Performancementioning
confidence: 62%
See 2 more Smart Citations
“…50 The analytes were also shown to have little degradation/loss in the sampling, transport and storage conditions of this study. 50 Therefore, the passive sampling system here is shown to have good QC. DGT sampling provides in situ TWA concentrations for the deployment period, e.g.…”
Section: Comparison Of Dgt and Grab Sampling Performancementioning
confidence: 62%
“…They are important ECs in river systems with well-developed DGT methods 23 and can be monitored using one DGT configuration (see sampler details later). 24,26,27,[48][49][50] Thirteen target chemicals were selected across EC types, as follows: S3 and their structures in Figure S3. Isotope-labelled chemicals were used as surrogate internal standards (SIS): SMX-d4, CAF-13C3, MEP-13C6, PRP-13C6, BUP-13C6, PHBA-d4 and E3-d2.…”
Section: Analytes Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…1–3 These advantages include the ability to obtain time-weighted average concentrations over a defined deployment period, simplified and cleaner sample extractions, 4 and stable and compact long-term freezer preservation of retrieved samplers. 5–7…”
Section: Introductionmentioning
confidence: 99%
“…Challis et al 18 found that biofilms did not appear to affect the uptake of a suite of pharmaceuticals and pesticides by comparing wastewater-deployed samplers with grab sampling concentrations. Recently, Wang et al 7 showed that biofouled hydrophilic polypropylene filter membranes deployed in wastewater for two weeks would not affect the application of DGT for some organic pollutants. However, analyte diffusivity may be greatly reduced by biofilms.…”
Section: Introductionmentioning
confidence: 99%